Nurses' beliefs about back pain, their coping strategies and participant activation for self-management - Loveness A. Nkhata; Yolandi Brink; Dawn Ernstzen; Diribsa Tsegaye; Quinnette Louw (AOSIS, 2022)
Background: Back pain affects nurses' physical, social and emotional well-being, as they encounter difficulties in executing their social and occupational duties. Objectives: Our study investigated the impact of a cross-cultural back pain campaign on nurses' beliefs about back pain; activating the participants to self-manage; coping strategies; sick leave claimed; and frequency of doctor visits. Method: A single sample pre- and post-test design was used. The intervention was a 12-week educational campaign based on evidence-based back pain messages. Primary outcomes were measured by their beliefs about back pain and their activation to self-manage. Analyses were conducted using SPSS version 27.0 software, and significant differences from before and after the campaign were analysed using the Chi-square test at a 0.05 significance level. Results: There were no significant differences in the age, gender and work hours of the nurses who participated before and after the campaign, except for their professional work settings ( 0.05). All secondary outcomes improved significantly after the campaign, and outcomes on beliefs about back pain showed significantly positive changes in six of the 14 items, while all questions pertaining to patient activation improved significantly. Conclusion: The 12-week back pain campaign, based on contextualised, evidence-based back pain messages for Zambian nurses, motivated the participants to self-manage their back pain. However, not all beliefs about back pain changed positively after the campaign. Clinical implications: The findings of this back pain education campaign show promise as a strategy to improve knowledge, behaviours and beliefs about back pain in African settings.